Pengembangan Media Pembelajaran Berbasis Android dan HTML Berbantu Lectora Inspire Pada Materi Jurnal Umum di SMK Muhammadiyah 04 Medan - Rizkianda, Chairina; Zainal, Andri; Haryadi, Haryadi; Sriwedari, Tuti; Ramdhansyah, Ramdhansyah (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
Innovation in creating learning media so that it can adapt to technological developments is an innovation that is needed in learning. This study aims to develop interactive learning media based on Android and HTML assisted by Lectora Inspire and then also analyze the feasibility, effectiveness and practicality of the media developed into general journal material. The development of this interactive learning media was developed using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection instruments used validation sheets, pre-test post-test sheets and also student response sheets. The material expert validation score was 94% with the very feasible category, the media expert validation score was 100% with the very feasible category, the learning practitioner validation score was 96.3% with the feasible category, and the user validation score was 98.1% with the very feasible category. With an average score of 97.1%, the media is considered very feasible to use. The practicality of the media gets a score of 82.15% which is in the very practical category, and the effectiveness of the media gets a score of 82.85% in the effective category.